2016
DOI: 10.1007/978-3-319-45550-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Round-off Errors in OpenMP Codes

Abstract: Abstract. It is crucial to control round-off error propagation in numerical simulations, because they can significantly affect computed results, especially in parallel codes like OpenMP ones. In this paper, we present a new version of the CADNA library that enables the numerical validation of OpenMP codes. With a reasonable cost in terms of execution time, it enables one to estimate which digits in computed results are affected by round-off errors and to detect numerical instabilities that may occur during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In this section, the CESTAC method is described and the algorithm of this method is presented. Also, a sample program of the CADNA library is demonstrated and finally advantages of the presented method based on the SA in discrete case are investigated in comparison with the traditional FPA [32,[34][35][36][37]40].…”
Section: Cestac Method-cadna Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the CESTAC method is described and the algorithm of this method is presented. Also, a sample program of the CADNA library is demonstrated and finally advantages of the presented method based on the SA in discrete case are investigated in comparison with the traditional FPA [32,[34][35][36][37]40].…”
Section: Cestac Method-cadna Librarymentioning
confidence: 99%
“…Graillat et al [38,39] studied the SA in multi precision, dynamical control of Newton's method for multiple roots of polynomials and numerical validation of compensated summation algorithms with SA. Eberhart et al [40] presented a high performance numerical validation using the SA. In recent years, the CESTAC method was applied to validate the results of several numerical methods such as estimating the value of interpolation polynomials [41], improper and definite integrals [42,43], dynamical control on Gauss-Laguerre integration rule [44], evaluating the fuzzy definite integrals [45], numerical validation of the Sinccollocation method to solve linear integral equations [46], finding optimal iteration of the power and inverse iteration methods, solving linear systems, fuzzy Newton-Cotes integration rules [47], finding the optimal parameter of the homotopy analysis method for solving integral equations [48], solving fuzzy integral equations [49], validating Taylorcollocation method for solving Volterra integral equations with discontinuous kernels [50] and load leveling problem [51].…”
Section: Introductionmentioning
confidence: 99%
“…Those advantages can be more pronounced on many-core processors. While CADNA supports OpenMP, the performance overhead can be larger than singlethread due to the existence of some private sections [8]. CADNA for CUDA is also available, but it is observed that the overhead (especially on compute-bound operations) becomes higher than that on CPUs [7].…”
Section: Matrix-vector Multiplication (Memory-bound)mentioning
confidence: 99%
“…A straightforward extension to this work would be the control of accuracy in quadruple precision parallel programs. CADNA can be used for the numerical validation of single or double precision parallel programs based on OpenMP [5] or MPI [17]. CADNA could be improved to enable the control of quadruple precision parallel programs: the main new features would be, with OpenMP the reduction operations with quadruple precision stochastic variables, and with MPI the exchange of this kind of variables between processors.…”
Section: Discussionmentioning
confidence: 99%